(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The research paper explores the concept of Web3, its implications for decentralization, user ownership, and empowerment. The paper provides an in-depth analysis of Web3’s impact on data ownership, privacy, and user control. It examines the role of blockchain technology and decentralized applications (DApps) in enabling a more decentralized internet ecosystem. The research highlights the contrasts between Web 2.0 and Web3, emphasizing the shift towards user-centricity and increased user empowerment. Challenges and considerations in Web3 adoption are discussed, along with future perspectives and potential applications in various industries.